Dacarbazine Combined Targeted Therapy versus Dacarbazine Alone in Patients with Malignant Melanoma: A Meta-Analysis - Jiang, Guan; Li, Rong-Hua; Sun, Chao; Liu, Yan-Qun; Zheng, Jun-Nian (PloS one, 2014)
Malignant melanoma is the most aggressive and deadly form of skin cancer. Dacarbazine (DTIC) has been the approved first-line treatment for metastatic melanoma in routine clinical practice. However, response rates with single-agent DTIC are low. The objective of this study was to compare the efficacy and safety of DTIC with or without placebo and DTIC-based combination therapies in patients with advanced metastatic melanoma. We searched from electronic databases such as The Cochrane Library, MEDLINE, EBSCO, EMBASE, Ovid, CNKI, and CBMDisc from 2003 to 2013. The primary outcome measures were overall response and 1-year survival, and the secondary outcome measurements were adverse events. Nine randomized controlled trials (RCTs) involving 2,481 patients were included in the meta-analysis. DTIC-based combination therapies was superior to DTIC alone in overall response (combined risk ratio [RR]  = 1.60, 95% confidence interval [CI]: 1.27-2.01) and 1-year survival (combined RR = 1.26, 95% CI: 1.14-1.39). Patients with DTIC-based combination therapies had higher incidence of adverse events including nausea (combined RR = 1.23, 95% CI: 1.10-1.36), vomiting (combined RR = 1.73, 95% CI: 1.41-2.12) and neutropenia (combined RR = 1.75, 95% CI: 1.42-2.16) compared to the group for DTIC alone. These data suggested that DTIC-based combination therapies could moderately improve the overall response and the 1-year survival but increased the incidence of adverse events. Further large-scale, high-quality, placebo-controlled, double-blind trials are needed to confirm this conclusion.